THE ROLE OF SELF-MANAGEMENT IN THE DEVELOPMENT OF INNOVATIVE PROJECTS IN THE ORGANIZATION - BILYK, Viktoriya; DEREVIANKO, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the course of writing the article, a growing interest in the problems of self-management in Ukraine was identified, which is caused by political and economic instability, the intensification of hostilities, and a decrease in the production capacity of organizations. The shortage of management approaches was analyzed and the need for new management strategies and methods was revealed, as traditional approaches are becoming insufficiently effective in the face of modern challenges. The progressive approach of organizations to emphasizing the creative potential and initiative of each employee is systematized, which contributes to the development of individual approaches to management. Self-management is defined as an effective tool for performing tasks with minimal costs and optimizing organizational processes. Optimal self-management skills were formed in the context of the organization’s innovative activities. A self-management system has been developed for the development of predefined skills of the innovation project team. The main problems and tasks of implementing self-management to ensure the success of innovative projects are characterized. Systematized the most effective modern tools for ensuring the effectiveness of self-management during the implementation of innovative projects, in particular, methods of structuring work processes and monitoring the performance of tasks and the latest tools for ensuring time management and quality communication. The role of self-management for achieving strategic goals and optimizing organizational productivity in the context of implementing innovative projects is summarized.